The impact of the timing of a prior year's auditor concessions on financial officers' judgments - Cheng, Mandy M. (2019)
Auditors and clients negotiate on financial statement numbers over time. In this study, we extend the existing literature on auditor-client negotiations by examining the judgments of client financial officers in a multi-period setting. We conduct an experiment to examine how an auditor's use of concession-timing strategies in the prior year influences financial officers' negotiation judgments in the current year. We find that financial officers report a larger expected ultimate income-decreasing audit adjustment and are prepared to offer more concessions if the auditor had previously used a concession-start strategy (where the auditor had given a concession before the start of the negotiation but did not concede during the negotiation) relative to a concession-end strategy (where the concession was provided only in the last round of negotiation). Our results indicate that auditors' prior negotiation strategies impact financial officers' use of strategies on current year's negotiations. Overall, these results suggest that findings in earlier single-period settings (e.g., Tan and Trotman 2010) potentially reverse in a multi-period setting.